Detection of t(14;18)(q32;q21) for IgH/BCL2 in central nervous system tumor‐like lesions with chronic perivascular inflammation. Issue 4 (13th September 2019) - Shishido‐Hara, Yukiko; Yazawa, Takuya; Chiba, Tomohiro; Kojima, Kaoruko; Ishii, Jun; Kobayashi, Keiichi; Lee, Jeung‐Hun; Sumiishi, Ayumi; Tsuchiya, Kazuhiro; Uchihara, Toshiki; Shiokawa, Yoshiaki; Takayama, Nobuyuki; et al.
Abstract: Objectives: There exist central nervous system tumor‐like lesions, resembling glioma on magnetic resonance imaging, although pathology shows active perivascular inflammation on biopsied brain tissues. As pathological diagnostic criteria have not been established, the nature of inflammatory cells was analyzed. Methods: Biopsied brain tissues from tumor‐like inflammatory lesions were first studied histopathologically. Inflammatory cells were evaluated with immunohistochemistry and fluorescence in situ hybridization, and their molecular features were also analyzed with BIOMED‐2 multiplex polymerase chain reaction and sequencing of polymerase chain reaction products. Results: Both B and T cells were infiltrated in the perivascular area, and BIOMED‐2 multiplex polymerase chain reaction detected the translocation t(14;18)(q32;q21); the fused IgH/BCL2 genes in all four patients. Fluorescence in situ hybridization showed juxtaposed IgH and BCL2 signals in 8% of perivascular cells in case 1, and 15% in case 4. Only a small number of cells were positive for CD10, BCL6 or MUM‐1; whether the translocation‐bearing cells were of nodal germinal center origin was not concluded. The fused IgH/BCL2 gene sequences were the same in four patients, which was contrasted with nodal follicular lymphoma with diversity in t(14;18)(q32;q21) patterns. Analysis of B‐cell receptor and did not show monoclonal proliferation of either B cells, but the T‐cell population appeared to be clonally restricted in one patient. Conclusions: The chromosomal translocation t(14;18)(q32;q21) for IgH/BCL2 was detected in central nervous system tumor‐like inflammatory lesions. All patients responded well to the corticosteroid therapy and had a good prognosis. As the perivascular cells bearing t(14;18)(q32;q21) are small in number, the pathological significance remains unknown. Abstract : Fluorescence in situ hybridization analysis of t(14;18)(q32;q21). Perivascular lymphoid cells showed translocation of t(14;18)(q32;q21) for IgH / BCL2, but the pathological significance remains unclear.